Knowledge management strategies adopted in agricultural research organizations in East Africa. (November 2021) - Akuku, Boniface; Waema, Timothy Mwololo; Oboko, Robert; Brown, Irwin
In previous studies, Knowledge Management (KM) strategies have been examined as objects of organizations, instead of scrutinizing their characteristics or relative quality and content. This study aims to examine the key characteristics of KM strategies in Agricultural Research Organizations (AROs) in East Africa in terms of what exists, what does not exist and why. To comprehensively answer the research questions and understand the phenomena under investigation the study adopted a pragmatism paradigm to allow facts and concerns to arise from the context. Qualitative and quantitative methods were employed using semi-structured Key Informant Interviews (KIIs) and a questionnaire respectively. A novel empirical description and explanation of the key characteristics of KM strategies in AROs in East Africa is presented. The study identifies the key concepts and gaps in the characteristics of KM strategies and elucidates what AROs in East Africa should do differently to coherently formulate and execute KM strategies in practice. The main characteristics of KM strategies in AROs in East Africa are practicability, technology-focus, alignment, implementation processes and relevance. Through abstraction and theorization of the key concepts, a detailed description and explanation as a reference for scholars and practitioners in the KM field is provided. Further, the study highlights context as an important and relevant perspective in particularizing the characteristics of a KM strategy and interpretation of related empirical findings. Future studies can use the concepts presented in this study to develop a theoretical framework for analyzing the characteristics of KM strategies in organizations. The idea of linking the study outcome to an empirical situation is a novel contribution. The findings of this study shed new insights that confirm that understanding characteristics of KM strategies is beneficial to practitioners and scholars.